An Engineered Prussian Blue Nanoparticles‐Based Nanoimmunotherapy Elicits Robust and Persistent Immunological Memory in a TH‐MYCN Neuroblastoma Model. Issue 8 (13th May 2021) - Shukla, Anshi; Cano-Mejia, Juliana; Andricovich, Jaclyn; Burga, Rachel A.; Sweeney, Elizabeth E.; Fernandes, Rohan
Abstract : A combination therapy using Prussian blue nanoparticles (PBNP) as photothermal therapy (PTT) agents coated with CpG oligodeoxynucleotides, an immunologic adjuvant, as a nanoimmunotherapy (CpG‐PBNP‐PTT) for neuroblastoma (NB) is described. NB driven by MYCN amplification confers high risk and correlates with a dismal prognosis, accounting for the majority of NB‐related mortality. The efficacy of the CpG‐PBNP‐PTT nanoimmunotherapy in a clinically relevant, TH‐MYCN murine NB model (9464D) overexpressing MYCN is tested. When administered to 9464D NB cells in vitro, CpG‐PBNP‐PTT triggers thermal dose‐dependent immunogenic cell death and tumor cell priming for immune recognition in vitro, measured by the expression of specific costimulatory and antigen‐presenting molecules. In vivo, intratumorally administered CpG‐PBNP‐PTT generates complete tumor regression and significantly higher long‐term survival compared to controls. Furthermore, CpG‐PBNP‐PTT‐treated mice reject tumor rechallenge. Ex vivo studies confirm these therapeutic responses result from the generation of robust T cell‐mediated immunological memory. Consequently, in a synchronous 9464D tumor model, CpG‐PBNP‐PTT induces complete tumor regression on the treated flank and significantly slows tumor progression on the untreated flank, improving animal survival. These findings demonstrate that localized administration of the CpG‐PBNP‐PTT nanoimmunotherapy drives potent systemic T cell responses in solid tumors such as NB and therefore has therapeutic implications for NB. Abstract : The nanoimmunotherapy mediates thermal dose‐dependent immunogenic cell death and tumor cell priming in neuroblastoma cells, leading to T cell activation and memory. These effects elicit long‐term, tumor‐free survival, and rejection of tumor rechallenge in a single tumor model of TH‐MYCN neuroblastoma, and a potent abscopal effect, leading to slower progression of untreated tumors in a synchronous tumor model.